2020
DOI: 10.3390/agronomy10111776
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Watermelon Nutrient Requirements Based on the QUEFTS Model

Abstract: Estimating balanced nutrient requirements for a watermelon plantation is essential to increase its fruit yield and nutrient use efficiency. This is vital for China, which produces 60% of world’s watermelons with excessive fertilizer application. Therefore, datasets between 2000 and 2019 from field experiments in major watermelon producing regions across China were collected to assess relationships between fruit yield and nutrient uptake, and to estimate nitrogen (N), phosphorus (P), and potassium (K) requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Application of the QUEFTS model to estimate the nutrient requirements of Chinese onion. On the basis of previous studies using QUEFTS for other crops (Chuan et al, 2013;Kang et al, 2020;Liu et al, 2006;Pathak et al, 2003;Ren et al, 2016;Saïdou et al, 2003;Setiyono et al, 2010;Sun et al, 2021;Witt et al, 1999;Xie et al, 2020;Xu et al, 2013aXu et al, , 2015Xu et al, , 2019Yang et al, 2017;Zhang et al, 2018Zhang et al, , 2019, the a and d values with the corresponding 2.5% of the upper and lower IE values removed were used as the parameters of the QUEFTS to estimate the nutrient requirements for Chinese onion. The results showed that a values of N, P, and K were 308.9, 782.7, and 2004.4 kg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Application of the QUEFTS model to estimate the nutrient requirements of Chinese onion. On the basis of previous studies using QUEFTS for other crops (Chuan et al, 2013;Kang et al, 2020;Liu et al, 2006;Pathak et al, 2003;Ren et al, 2016;Saïdou et al, 2003;Setiyono et al, 2010;Sun et al, 2021;Witt et al, 1999;Xie et al, 2020;Xu et al, 2013aXu et al, , 2015Xu et al, , 2019Yang et al, 2017;Zhang et al, 2018Zhang et al, , 2019, the a and d values with the corresponding 2.5% of the upper and lower IE values removed were used as the parameters of the QUEFTS to estimate the nutrient requirements for Chinese onion. The results showed that a values of N, P, and K were 308.9, 782.7, and 2004.4 kg/kg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Both onion stem and onion leaves are edible and are regarded as economic yield. Therefore, the harvest index of Chinese onion in the study was 1, whereas other crops such as corn, peanuts, radishes, and watermelons are divided into economic and noneconomic yield, and the harvest index is 0.18 to 0.82 (Kang et al, 2020;Xie et al, 2020;Xu et al, 2015;Zhang et al, 2019). For Chinese onion with harvest index of 1, it is more convenient to use the QUEFTS model to simulate the nutrient requirements and the simulation is also more accurate, which was verified in field experiments in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Another model, that can be used for different crop types, is the QUEFTS (QUantitative Evaluation of the Fertility of Tropical Soils) model [ 22 ], that can be used for the estimation of crop yield by given soil properties and the amount of applied fertilizer. This model has been used for potato [ 23 ], as well as for other crops [ 24 , 25 ]. In addition, considering other crops, it is worth noting that today there are also a number of models for the simulation of fruit tree development [ 26 ].…”
Section: Introductionmentioning
confidence: 99%